The Impact of the Covid-19 Pandemic on Banking Risks and Performance - Susilo Surahman; Irsyad Kamal; Renya Rosari; Etty Susilowati; Pandu Adi Cakranegara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims at analyzing banking risks and performance during the COVID-19 pandemic which will affect the soundness of the bank. In this study, the researchers applied the qualitative method by examining the condition of natural objects, positioning the researchers as the key instrument, applying triangulation (combination) in the data collection, and analyzing data inductively. The analyzed data in this study was collected by implementing library research, which is a study carried out by collecting data from books, journals, articles, magazines, and internet sources related to research problems. The collected data from internet sources were in the form of stock price data and transaction volume at banks on the Indonesia Stock Exchange. Those data were obtained from idx.co.id and ojk.go.id. Results of this study indicate that all banks tend to experience a decline in the value of risk-weighted assets, capital adequacy ratios, and interest income at each bank and sectoral level. Moreover, larger banks are relatively more vulnerable. The decrease in those three dimensions is predicted to increase disproportionately if the NPL shock becomes larger. The findings further suggest that a 10% NPL shock can force the capital adequacy of all banks to fall below the BASEL III minimum requirement, while a shock of 13% or more can turn it into zero or negative at the sectoral level. Apart from that, the call to stay at home has an impact on many sectors, especially the banking sector, so that financing growth slows and non-performing financing increases because many people have lost their jobs. This non-current financing definitely will have an impact on banking financial performance, leading to non-performing financing (NPF).